2002
DOI: 10.1258/002221502760132665
|View full text |Cite
|
Sign up to set email alerts
|

Nasal septal abscess: an unusual complication of acute spheno-ethmoiditis

Abstract: Nasal septal abscess complicating acute sinusitis is rare. There have been very few reports in the literature of this condition. We present a 12-year old-male with a nasal septal abscess complicating acute pansinusitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
33
0
9

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 8 publications
1
33
0
9
Order By: Relevance
“…The imaging findings of nasal septal abscess, a thin-walled fluid collection with adjacent inflammatory change, are similar to those seen with abscesses located elsewhere within the body. Pang et al 3 reported a case of nasal septal abscess as an unusual complication of acute spheno-ethmoiditis with similar imaging findings of a thin-walled, enhancing fluid collection involving the cartilaginous and bony septum.…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…The imaging findings of nasal septal abscess, a thin-walled fluid collection with adjacent inflammatory change, are similar to those seen with abscesses located elsewhere within the body. Pang et al 3 reported a case of nasal septal abscess as an unusual complication of acute spheno-ethmoiditis with similar imaging findings of a thin-walled, enhancing fluid collection involving the cartilaginous and bony septum.…”
Section: Discussionmentioning
confidence: 87%
“…2 Surgical drainage of the purulent contents of a nasal septal abscess is performed to relieve pressure and to provide a specimen for Gram stain, culture, and sensitivity. Nasal packing, the placement of a Penrose drain, 3 reduction of nasal fractures, and delayed reconstruction of destroyed nasal cartilage 2 may also be performed. The results of Gram stain and culture and sensitivity of the aspirate determine the appropriate systemic antibiotic coverage.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations